Review of insect pathogen risks for the black soldier fly (Hermetia illucens) and guidelines for reliable production. Issue 6 (8th June 2020) - Joosten, Lotte; Lecocq, Antoine; Jensen, Annette Bruun; Haenen, Olga; Schmitt, Eric; Eilenberg, Jørgen
Abstract: Black soldier fly [BSF; Hermetia illucens L. (Diptera: Stratiomyidae)] larvae are very effective in transforming low‐grade food waste into valuable high‐end proteins and fat, in intensive production facilities. The production output of this species is growing quickly, but upscaling brings risks to the health status of the reared insects. Until now, not a single major case of disease outbreak caused by a pathogen in a BSF production unit has been reported. This contrasts with data on other species of mass‐produced insects, which have experienced various disease outbreaks, indicating that BSFs are comparatively resistant to insect diseases. Further, there are no records of natural infections caused by entomopathogens in BSF. In this review, the known entomopathogens of Diptera, especially BSF, and their potential risks for causing disease in these insects are summarized. Abstract : The black soldier fly (BSF) (Diptera: Stratiomyidae) production output is growing quickly, but upscaling brings risks to insect health. Up to now, not a single case of disease outbreak caused by an insect pathogen in a BSF production unit has been reported, nor any records of natural infections of BSF. In this review the known entomopathogens of Diptera, especially BSF, and their potential risks for causing disease in these insects are summarized.